Silyl Formates as Surrogates of Hydrosilanes and Their Application in the Transfer Hydrosilylation of Aldehydes. Issue 45 (10th October 2016) - Chauvier, Clément; Thuéry, Pierre; Cantat, Thibault
Abstract: Silyl formates are investigated for the first time as surrogates of hydrosilanes. In the presence of a well‐defined ruthenium catalyst, these reagents are shown to promote the chemoselective reduction of a variety of aldehydes by transfer hydrosilylation. Mechanistic investigations have shown that genuine hydrosilane species are avoided during catalysis. The mechanism involves a sequence of decarboxylation/insertion/transmetallation steps. Abstract : Surrogate family : Silyl formates are investigated for the first time as surrogates of hydrosilanes. These reagents, obtained from formic acid and chlorosilanes, are shown to promote the chemoselective reduction of a variety of aldehydes, using ruthenium molecular catalysts. The reaction proceeds by transfer hydrosilylation, with concomitant release of CO2 .